Chinese learner in a linguistically challenged environment – an exploratory study. Issue 2 (8th May 2018) - Wong, Grace; Dellaportas, Steven; Cooper, Barry J.
Abstract : Purpose: The purpose of this paper is to explore the implications for student learning when accounting education is delivered in the student's non-native language. It examines the impact on learning arising from the different components of English language competencies, namely, listening, reading, writing, and speaking. Design/methodology/approach: The data are drawn from focus group interviews with students from Mainland China undertaking an accounting degree in Australia. Findings: The findings indicate that students relied primarily on their reading instead of listening to seek understanding, and in turn, writing was considered less important compared to listening and reading. Notably, speaking was overlooked by many students as it was considered the least important skill necessary to achieve success as a student and to be a competent practitioner. Students developed a misconception that the quality of oral communication required of accountants in practice is unimportant. Practical implications: The findings will assist accounting educators and the accounting profession in designing and implementing appropriate instructional strategies and assessment tasks for international students. One suggestion includes a more balanced weighting between written and oral assessment. Originality/value: Few studies have specifically explored the impact of English language on learning accounting. While some studies examine specific aspects of language as a unitary concept, little has been reported on the impact of all components of the language skill-set on student learning.